Pengaruh Kompensasi dan Lingkungan Kerja Terhadap Kinerja Perawat Rumah Sakit Cinta Kasih Tzu Chi dengan Motivasi Kerja Sebagai Variabel Intervening - Suriadi Suriadi; MF. Arrozi Adhikara; Andry Andry (Syntax Corporation Indonesia, 2022)
Excellent service quality needs to get the main attention in the provision of services in hospitals, for that it is important to improve the performance of nurses as the spearhead of service. This study aims to analyze the effect of compensation and work environment on the performance of nurses at Cinta Kasih Tzu Chi Hospital with work motivation as an intervening variable. This research is a quantitative study with hypothesis testing, carried out in October 2021 - December 2021 with a total of 118 nurses as respondents. Hypothesis testing using path analysis structural equation model (Structural Equation Model. The results show that compensation, work environment and work motivation have a significant effect on nurse performance. Partial test results are as follows: compensation has a significant positive effect on work motivation, work environment has a significant positive effect on motivation work, compensation has a significant negative effect on nurse performance, work environment has a significant positive effect on nurse performance, and work motivation has a significant positive effect on nurse performance.The results of this study are in line with the theory expressed by Bernaddin and Russel (1993) about factors that can affect performance. employees include work motivation and factors that can affect work motivation include compensation and work environment Managerial implications: hospital management needs to improve the employee remuneration system, develop a reward system in the form of intrinsic compensation and improve the hospital governance system that refers to improving the work environment